Dual-Band Dual-LP/CP Antennas Using Combined Metasurface and Patch For UHF/2.45-GHz RFID Readers - Thi Ngoc Hien Doan; Khac Kiem Nguyen; Son Xuat Ta (IEEE Access, 2024)
This paper proposes dual-band dual linearly-polarized (LP)/circularly-polarized (CP) antennas using combined metasurface and patch for ultra high frequency (UHF) and 2.45-GHz RF identification (RFID) readers. A metasurface and two stacked patches are employed for the lower and upper bands, respectively. The metasurface and patches are incorporated with a common feeding structure which is composed of two orthogonal microstrip lines and a crossed slot to produce the dual-wideband dual-LP radiation. To reduce the back radiation and improve the gain, the antenna is backed by a metallic cavity. Taking advantage of its low-profile structure, the dual-LP antenna is further integrated with a dual-band branch-line coupler to realize dual-CP radiation. Both proposed antennas yield stable radiation performances across dual operating bands which completely cover the assigned RFID spectrum at the UHF ( $860-960$ MHz) and 2.45-GHz ( $2400-2500$ MHz) bands.